Effectiveness of Mind-Body Interventions on Stress Reduction and Body Awareness - Ahmmed, Badhon; Khan, Ayesha (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective:  This study aimed to evaluate the effectiveness of a structured mind-body intervention in reducing perceived stress and enhancing body awareness among adults.Methods and Materials: The study used a randomized controlled trial design with 30 adult participants from Pakistan, randomly assigned to either an intervention group (n = 15) or a control group (n = 15). The intervention group received nine weekly sessions of a structured mind-body program incorporating mindfulness practices, breathwork, progressive muscle relaxation, and mindful movement, while the control group received no psychological training during this period. Both groups completed assessments at three time points: pre-test, post-test, and three-month follow-up. Perceived stress was measured using the Perceived Stress Scale (PSS), and body awareness was assessed using the Body Awareness Questionnaire (BAQ). Data were analyzed using repeated measures ANOVA with Bonferroni post-hoc tests in SPSS-27.Findings: The intervention group showed a significant reduction in perceived stress from pre-test (M = 28.47, SD = 3.92) to post-test (M = 17.26, SD = 4.21), which was sustained at follow-up (M = 18.02, SD = 4.33), while the control group showed no meaningful change. Similarly, body awareness scores in the intervention group increased significantly from pre-test (M = 62.13, SD = 6.48) to post-test (M = 77.94, SD = 5.87) and remained elevated at follow-up (M = 76.80, SD = 6.03), with no substantial changes in the control group. Repeated measures ANOVA revealed significant time, group, and interaction effects (p < .001), with large effect sizes. Bonferroni post-hoc analysis confirmed the stability of changes from post-test to follow-up.Conclusion: The findings suggest that mind-body interventions are effective in reducing stress and increasing body awareness, with sustained effects over a three-month period, making them a promising approach for psychological and somatic well-being in general adult populations.